2006
DOI: 10.1159/000092912
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Characteristics and Outcome of Adult Patients with Hematuria and/or Proteinuria Found during Routine Examination

Abstract: Background: Patients with hematuria and/or proteinuria found during routine examination are commonly encountered. To define the clinicopathological characteristics and outcome of these patients, 142 patients with definite pathological diagnosis were studied retrospectively.Methods: All the 142 patients were divided into three groups: pure hematuria (HU, n = 13), concomitant hematuria and proteinuria (HUPU, n = 79), and proteinuria alone (PU, n = 50). Results: At the time of renal biopsy, 26% of the patients ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The rising level of urinary erythrocytes might indicate a high degree of glomerular inflammation in the early course of renal disease and were found associated with renal function deterioration (21). Recently, several authors demonstrated that patients with persistent microscopic haematuria had a poor prognosis, particularly those with development of proteinuria and hypertension (22,23). Hence, more attention should be paid to adult patients with IMH, because their prognosis may not be optimistic.…”
Section: Discussionmentioning
confidence: 99%
“…The rising level of urinary erythrocytes might indicate a high degree of glomerular inflammation in the early course of renal disease and were found associated with renal function deterioration (21). Recently, several authors demonstrated that patients with persistent microscopic haematuria had a poor prognosis, particularly those with development of proteinuria and hypertension (22,23). Hence, more attention should be paid to adult patients with IMH, because their prognosis may not be optimistic.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, patients with persistent hematuria and/ or mild proteinuria found during routine examination in children and adults are commonly encountered. 4,5 Hence, late referral for this disease to a physician or a nephrologist when there is a reduction in the renal function is often common. Currently, renal biopsy remains the standard invasive approach for diagnosing IgAN.…”
mentioning
confidence: 99%
“…Some studies use urinalysis alone to screen for early stage CKD; this simplifies analysis in a variety of different populations [18,19,20,21,22]. In particular, proteinuria has been associated with renal outcome [23]. Those studies found that urinalysis was valuable for renal function analysis.…”
Section: Discussionmentioning
confidence: 99%